Digital transformation in Romanian accounting practice and education: Impact and perspectives - Gina Raluca Guşe; Marian Dragoș Mangiuc (Amfiteatru Economic Journal, 2022)
Transformation of business models using digital technologies is depicted by the European Green Deal (EC, 2019) as a key factor in achieving sustainability goals. For the business environment, the digitalization of organizations entails changes in the accounting functions, correlated with the increase in the volume and nature of managed data. In this paper, we analyse the impact of digital technologies in the field of accounting. We also investigate the degree of adequacy of the Romanian higher education system to the educational needs associated with the digital skills required of professional accountants from different generations. We use data collected from the curricula of business bachelor's programs from the four largest university cities in Romania. Results illustrate the universities' potential for training specialists to assimilate and steer the digital transformation of the accounting profession.
Keywords: I25; M14; M15; M41; 330; Digitalization; accounting education; European Green Deal; Romania